Relatório de Estágio Profissional "O meu percurso na viagem para me tornar Professora de Educação Física" - Marta Alexandra Oliveira Costa (2017)
This report is based on everything I experienced throughout the Professional Internship, included in the second year of the Master's Program in Teaching Physical Education in Elementary and Secondary Education of the Faculty of Sport of the University of Porto. This document contains an account of the activities developed over the school year, confronting theory with practice. This curricular unit incorporates two components: the supervised teaching practice, carried out at a cooperating school, under the guidance of a cooperating teacher and the internship report, elaborated with the guidance of a faculty member. The traineeship report is divided into five parts: (1) Introduction - brief contextualization of this document; (2) Personal Framing - My life course and the reasons that led me to choose to integrate this master's degree as well as my initial expectations; (3) Professional Practice Framework - Legal and institutional - as well as a brief characterization of the cooperating school and internship nucleus; (4) Professional Practice - account of my experience throughout the professional stage divided into three areas of performance: Area 1 - Organization and Management of Teaching and Learning, Area 2 - Participation in School and Community Relationships and Area 3 - Professional development. In this chapter, a number of themes emerged that became crucial to me throughout the year, as well as the research paper entitled " Is the students' commitment indispensable for their evolution?" In which I found that the most committed students showed significant developments; (5) Conclusion - Summary of the school year activities, my evolution as a teacher and expectations for the future.